METODE STANDARD SETTING UNTUK UJIAN NASIONAL DI SEKOLAH DASAR - Rejeki, Sri; Mardapi, Djemari; Kumaidi, Kumaidi (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2014)
Penelitian ini bertujuan mengetahui karakteristik hasil Cut Score UN di SD tahun 2009 berdasarkan pengembangan implementasi metode Nedelsky, Ebel, Bookmark dan hasil modifikasi metode Ebel-Bookmark; eyakinan panelis terhadap implementasi metode Standard Setting untuk menetapkan Cut Score; dan akurasi implementasi berdasarkan standar deviasi masing-masing metode. Sampel meliputi 10 orang panelis pada putaran 1, 16 guru pada putaran 2, 8 pakar dan 1650 hasil pekerjaan siswa. Prosedur dan análisis data mengikuti langkah empat metode yang ditetapkan. Analisis item menggunakan program ITEMAN dan Bilog MG dengan 1 Parameter Logistik. Berdasarkan hasil analisis data disimpulkan (1) Rerata Cut Score berdasarkan metode Nedelsky untuk mata pelajaran Bahasa Indonesia 28,44, Matematika 23,47, IPA 27. Metode Ebel untuk Bahasa Indonesia 80,75, Matematika 60,21, IPA 77,54. Metode Bookmark untuk Bahasa Indonesia sebesar 51,63, Matematika 51,33, IPA 59,16. Modifikasi Ebel-Bookmark untuk Bahasa Indonesia 81,27, Matematika 79,06 dan IPA 77,44; (2) keyakinan panelis dalam implementasi metode Standard Setting untuk metode Bookmark 81,25%, modifikasi Ebel-Bookmark 62,50%, metode Ebel 43,75% dan metode Nedelsky 43,75%; (3) Metode Bookmark lebih akurat dalam menetapkan cut score mata pelajaran Bahasa Indonesia dan Matematika, modifikasi metode Ebel-Bookmark lebih akurat untuk menetapkan cut scoremata pelajaran IPA.Kata kunci: standard setting, ujian nasional, sekolah dasar______________________________________________________________ THE STANDARD SETTING METHOD FOR THE NATIONAL EXAMINATION IN THE ELEMENTARY SCHOOLAbstract This study aims to investigate the characteristics results in Cut Score of UN elementary school in 2009 based on developing the implementation of Nedelsky, Ebel, Bookmarks methods, and modified Ebel method-Bookmark; panelists' confidence on the implementation of the methods for setting the Standard Setting Cut Score; and the implementation's accuracy based on the standard deviation of each method. The sample included 10 panelists in round 1, 16 teachers in round 2, 8 experts, and 1650 students' work. Procedures and analysis of data followed the steps of four methods specified. Item analysis used the program ITEMAN and Bilog MG with 1 Parameter Logistic. Based on the results of data analysis it is concluded 1). Cut Mean Score based on Nedelsky method for Indonesian is 28.44, Math is 23:47, and Science is 27. Ebel methods for Indonesian is 80.75, Mathematics is 60.21, and Science is 77.54. Bookmark method for Indonesian is 51.63, Mathematics is 51.33, Science is 59.16. Modified Ebel-Bookmark for Indonesian is 81.27, Mathematics is 79.06, and Science is 77.44; 2). panelists confidence in the implementation of the Standard Setting of Bookmark method is 81.25%, Ebel-modification Bookmark is 62.50%, Ebel methods is 43.75%, and methods Nedelsky is 43.75%; 3).The Bookmark method is more accurate in determining the cut score for Indonesian Language and Mathematics, modified Ebel- Bookmark method is more accurate to establish the cut score for the science subject. Keywords: Standard Setting, National Examination, elementary school